Qing-Fei-Pai-Du Decoction ameliorated coagulopathy and thrombocytopenia in endotoxaemia rats and enhanced platelet production from megakaryocytes - Jiao Wu; Pei-Chun Wang; Qiong-Sen Wang; Wei-Dong Zhang; Yue-Juan Zheng; Xuan Liu (Elsevier, 2023)
Backgrounds: The Qing-Fei-Pai-Du Decoction (QFPDD) was reported to ameliorate the inflammatory coagulopathy and thrombocytopenia in COVID-19 patients. This work investigated the effects of QFPDD in endotoxaemia rats and then further studied its influence on platelet production using cultured megakaryocytes. Methods: The coagulation indexes and platelet aggregation reactivity of LPS-induced endotoxemia rats with or without QFPDD treatment were analyzed. The platelet parameters, the expression of thrombopoietin (TPO) in the liver and the kidney, number of the megakaryocytes in bone marrow smear of rats were checked. The maturation and platelet production of human megakaryoblastic MEG-01 cells treated with QFPDD or isochlorogenic acid A (ISA), an active component of QFPDD, were observed. Results: QFPDD improved the coagulation indexes of LPS-induced endotoxaemia rats and decreased the hyper-reactivity of platelets. QFPDD ameliorated LPS-induced decrease in platelet number, partially alleviated increase in liver TPO expression and exhibited no influence on increase in the number of bone marrow megakaryocytes. QFPDD promoted maturation and production of platelet-like particles of MEG-01 megakaryocytes. The effects of QFPDD on MEG-01 megakaryocytes might be related to activation of AKT pathway and up-regulation of related transcription factors. ISA also could induce the maturation of MEG-01 cells. Conclusions: QFPDD effectively ameliorated coagulopathy and thrombocytopenia in rats under inflammatory state. The mechanisms of QFPDD in ameliorating thrombocytopenia might be based on both decreasing effects on platelet depletion in coagulation and inducing effects on maturation and platelet production of megakaryocytes. ISA might be one of the components which contribute to the effects of QFPDD on megakaryocytes.